Variation in water surface area and its impacts on bat drinking activity in an urban environment - Peyton E. Harper; Victoria J. Bennett (Frontiers in Ecology and Evolution)
The availability and accessibility of water resources are important factors influencing bat presence in urban areas. As bats drink ‘on the wing’, total surface area of a water sources determines overall water availability, but the presence of clutter dictates water accessibility. Understanding how water accessibility influences bat resource use may therefore provide a more accurate measure of water availability in urban environments. To explore this, we assessed how variation in water surface area influenced bat activity and species richness in an urban area. We conducted surveys at six study sites in Tarrant County, Texas, USA in 2023 and 2024 using a thermal camera to measure the total duration of bat presence and the number of drinking events. Additionally, we used an acoustic detector to record the number of species recorded drinking at the sites during each survey. A drone was used to evaluate water surface area metrics, including fundamental and realized surface areas, maximum patch sizes, and the longest stretches of continuous area. Our findings indicated that decreasing the length of available surface was associated with reduced bat activity. Notably, drinking activity, a key indicator of water resource use, declined with increasing clutter due to litter, emergent vegetation, algal blooms, and even fallen trees. These results suggest that the presence of clutter, in particular, may limit and even prevent bats from accessing water. Effective management of urban water sources should prioritize clutter removal to improve water accessibility for bats and support a diverse urban wildlife community.